ANALISIS PENGGUNAAN BUSI RACING TERHADAP UNJUK KERJA MESIN TOYOTA AVANZA 1300 CC - Budi Harjanto; Lumintang , D.Ricky; Budi Santoso, Edy (JURNAL MEKANIKASISTA, 2023)
To overcome this is certainly a need to increase engine performance either by the use of spark plugs can improve the performance of a gasoline engine. Thus improve fuel efficiency and reduce exhaust gas emissions such vehicles. In the spark ignition engine, the spark plug serves to provide a gap in the combustion chamber so that high-voltage electrical pulses to flow out which will further ignite the mixture in the surrounding areas and then move extends throughout the mass of the mixture in the combustion chamber. No wadays many emerging racing spark plugs are made of iridium alloy with a variety of brands that can improve performance and reduce fuel consumption and exhaust emissions.Test object used is the official vehicle of Toyota Avanza 1300cc. In this study, the machine uses an ignition angle 120 and the fuel used is pertamax octane 92. To determine the increase in torque, power, specific fuel consumption and thermal efficiency of the engine speed is used varies from 1800 rpm, 2000 rpm, and up 2300 rpm.Results showed increased engine performance along with increasing rpm. However, a significant improvement and efficient is shown at speed below 2500 rpm in the use of a standard spark plug of 7,852 kg.m torque, 21,96 PS of power, 0,225 specific fuel consumption, and 26,25% of the thermal efficiency at speed 2000 rpm. This is due to the condition of the test equipment used is relatively old and his condition is not normal that rotation variation used is limited, only at low speed only while iridium spark plugs itself will achieve peak performance and efficient in fuel consumption in high rotation above 6000 rpm. Therefore the use of standard spark plugs is more effectively used on the machine Toyota Avanza 1300cc because the machine is a machine with low compression with factory setting (standard) so it is not compatible when using modern spark plugs with high technology such as racing spark plugs.